Results of surgical treatment of patients with acute destructive diverticulitis of the colon using minimally invasive technologies - O.B. Tymchuk; S.L. Malinovskyi (Medičnì Perspektivi)
Among the diseases of the colon, diverticular disease occupies one of the leading positions, the frequency of which is currently 1.2 cases per 1000 people. Complications in this condition develop in 5% of cases and account for 3-5% of all patients with acute abdominal diseases. Surgical intervention is required in 15% to 30% of such patients. The mortality rate after surgical treatment of acute complications of the diverticular disease remains high, ranging from 7% to 25%. The purpose of our study was to compare the outcomes in the treatment of patients with acute destructive diverticulitis of the colon using traditional surgical treatment versus minimally invasive technologies. In the study, 114 patients diagnosed with acute destructive diverticulitis were examined. Group I consisted of 56 patients who underwent initial surgical interventions employing minimally invasive methods like laparoscopy, laparoscopic-assisted techniques, or percutaneous drainage guided by ultrasound. Group II comprised 58 patients who underwent the first surgical intervention through laparotomy access. The data of our study show that the overall proportion of patients with complications was higher in Group II – 20 (34.5%) compared to 6 (10.1%) in Group I (p=0.005). The application of diverse surgical methods did not notably impact the mortality rate, with 6 (10.3%) fatalities in Group II compared to 2 (3.6%) in Group I (p=0.2). Stoma creation was more frequent in Group II, in 40 (67%) patients, whereas in Group I, the occurrence of stomas was lower, in 15 (25.9%) cases. The average period to stoma closure was 5 months in Group II and 2 months in Group I. There was observed a decrease in the time of urgent surgery from 143±13.5 minutes in Group II to 65.7±15.2 minutes in Group I (p<0.01) and the duration of the first hospitalization from 14.2±1.8 days to 5.6±0.7 days, accordingly (p<0.01). When dealing with primary anastomosis or severe peritonitis, utilizing a laparoscope for dynamic laparoscopy allows for real-time monitoring of the abdominal cavity and early identification of complications, eliminating the need for scheduled laparostomy. The research data demonstrate that, while not affecting mortality, minimally invasive methods have several significant advantages, including a reduction in the number of complications, a decrease in the proportion of patients with stomas, a reduction in the time to reconstructive surgery, and a decrease in the duration of urgent surgery and the length of hospitalization.